2016
DOI: 10.4103/0975-962x.180318
|View full text |Cite
|
Sign up to set email alerts
|

The facial skeleton: Armor to the brain?

Abstract: Background:With the development of urban setting worldwide, the major issue of concern is the increase in the mortality rate in the population due to road traffic accidents. The face, being the most exposed region is susceptible to injuries and maybe associated with injuries to the adjacent neuro-cranium. The literature has conflicting views on the relationship between facial fractures and head injuries with some authors opining that the facial skeleton cushions the brain while some other authors claim that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The epidemiological criteria revealed that maxillofacial fractures accounted for 4% of all trauma cases, and its peak was at the year 2011 and 2015; this result is slightly higher than that reported by Pillay et al which reported the incidence of craniomaxillofacial fractures as 2.9% (Pillay et al 2018), but lower than that previously reported (16%) in a similar study conducted in Australia (Shahim et al 2006). The incidence of traumatic head injury (THI) associated with MFF in different countries around the world is greatly different, but the overall result is higher in males when compared with females; in the present study, it is 7:1; this result is in accordance with Patil et al (2016). Other studies in the developed countries, the male/female ratio ranged from 2:1 to 4:1, which indicates the active participation of women in outdoor life activities than in developing countries (Gassner et al 2003).…”
Section: Discussionsupporting
confidence: 88%
“…The epidemiological criteria revealed that maxillofacial fractures accounted for 4% of all trauma cases, and its peak was at the year 2011 and 2015; this result is slightly higher than that reported by Pillay et al which reported the incidence of craniomaxillofacial fractures as 2.9% (Pillay et al 2018), but lower than that previously reported (16%) in a similar study conducted in Australia (Shahim et al 2006). The incidence of traumatic head injury (THI) associated with MFF in different countries around the world is greatly different, but the overall result is higher in males when compared with females; in the present study, it is 7:1; this result is in accordance with Patil et al (2016). Other studies in the developed countries, the male/female ratio ranged from 2:1 to 4:1, which indicates the active participation of women in outdoor life activities than in developing countries (Gassner et al 2003).…”
Section: Discussionsupporting
confidence: 88%
“…9,10 Of the different types of brain injury, an association between ZMO fractures and subdural hematomas (SDHs) has been identified in the literature, 11 and brain injury frequencies of up to 61.0 to 67.0% have been reported in patients diagnosed with ZMO fractures. 12,13 The literature has clearly focused on the need for surgical intervention in ZMO fractures, and the authors are not aware of comparative publications focusing on the relation between AIs and ZMO fractures in geriatric patients with facial trauma.…”
mentioning
confidence: 99%
“…FISS> 5 has a 18-fold longer predictive value, need for internal fixation, and multiprofession-related interventions FISS has more multitrauma faces and intracranial lesions that require surgical protection. 30,31 The results of the study by Nasser F have an important relationship between FISS scores with surgery. Research by Aita and colleagues, also stated that patients with a FISS score> 5…”
Section: Discussionmentioning
confidence: 98%
“…29 Whereas male gender is dominant than female, namely (4: 1) while Bagheri SC et al with a ratio (3: 1) because workers are dominated by men rather than women. Men have physical activity and are often involved in violence 30 . In terms of work, women work a lot at home, but if women's work is the same as men's work, then women can have this risk.…”
Section: Discussionmentioning
confidence: 99%